Education for a knowledge society in Arabian Gulf countries - Alshumrani, Saleh; Alromi, Naif H.; Wiseman, Alexander W., 1968- (Bingley, U.K. : Emerald, 2014)
The worldwide shift towards a knowledge society and information based economy requires educational policy makers to re-evaluate their understanding of the knowledge and skills students need in order to achieve national development goals. This shift has influenced curriculum development, teacher preparation, and the role of formal schooling in creating lifelong learners and an educational culture, which reflects both national development interests and global norms. The Arabian Gulf countries, which largely comprise the Gulf Cooperation Council (GCC) member countries, include Bahrain, Kuwait, Oman, Qatar, Saudi Arabia, the United Arab Emirates, and Yemen. Most of these Gulf countries have embarked on bold national experiments to pilot technology and teaching in their schools as a way to transition to knowledge societies. Their national interests and expectations have increasingly focused on the use of information and communication technologies (ICT) in education and both the regional and global context in which Gulf societies, economies, and political systems operate.
Challenges to creating an Arabian Gulf knowledge economy / Alexander W. Wiseman, Naif H. Alromi, Saleh Alshumrani -- Philosophy, language policy and the knowledge society / Arfan Ismail -- Education, development and sustainability in Qatar : a case study of economic and knowledge transformation in the Arabian Gulf / Alan S. Weber -- Building a knowledge society on sand : when the modernist project confronts the traditional cultural values in the Gulf / Michael Lightfoot -- From centralized education to innovation : cultural shifts in Kuwait's education system / Ilene K. Winokur -- The "Singapore of the Middle East" : the role and attractiveness of the Singapore model and TIMSS on education policy and borrowing in the Kingdom of Bahrain / Daniel John Kirk -- Postgraduate students perceptions toward online assessment : the case of the faculty of education, Umm Al-Qura university / Mohamed Abdelraouf Attia -- New horizons of integrating ICTs in Egyptian initial teacher education / Hanan Salah EL-Deen Mohamed EL-Halawany -- The impact of socioeconomic status on students achievement in the Middle East and North Africa : an essay using the TIMSS 2007 database / Donia Smaali Bouhlila -- Making the transition to a knowledge economy and knowledge society : exploring the challenges for Saudi Arabia / Fiona Patrick -- University roots and branches between "glocalization" and "mondialisation" : Qatar's (inter)national universities / Justin J.W. Powell -- Strategically planning the shift to a Gulf knowledge society : the role of big data and mass education / Alexander W. Wiseman.
Includes index.
Print version record
Keywords: Education -- Administration -- General; Educational strategies & policy; Organization & management of education; Education and state -- Persian Gulf Region; Technology -- Study and teaching -- Government policy -- Persian Gulf Region; Knowledge economy -- Persian Gulf Region; Economic development -- Effect of education on -- Persian Gulf Region; Labor supply -- Effect of education on -- Persian Gulf Region